Qualitative Phytochemical Screening, Investigation of Macro Minerals and Antimicrobial Activity of Leaves and Stem Extracts of Delonix Regia medicinal Plant - Atul K. Wanjari (International Journal of Pharma and Bio Sciences, 2020)
Biologically active compounds are present in medicinal plants which are used for the treatment of various diseases. The aim of the present study is to find out the phytochemical constituents and metal ions present in the stem and leaf extract of Delonix regia plant and to study its antimicrobial activity. The objective of the present study is to extract the phytochemical constituents in various organic extracts using soxhelt extraction process and also to study the presence of various macro minerals present in the extract using a flame photometer. This encourages efforts to continue and explore natural materials that can be used as new antimicrobial drugs against various bacteria. In order to achieve the aim of the present study, four different solvents were used, namely DMSO, Chloroform, Ethyl acetate, Propan-2-ol, water as a solvent medium. Extraction was done using soxhlet apparatus. Total 20 phytochemical constituents were investigated in the present study. Macro minerals like sodium, potassium, and calcium were investigated from the extracts by using flame photometer on the basis of colour of flame. The extract was screened against the gram positive and gram negative bacteria like E. coli, S. typhi, S. abony, P.aeruginosa, and B. subtilis for the antimicrobial study. The leaves and stem extract contain saponin, alkaloid, terpenoids, flavonoids, steroids, cardiac glycosides, quinine, coumarins, Tannins etc. FT-IR analysis detected –OH, carbonyl, -NH functional groups in the extract. The results show that the presence of reducing sugar phenols, terpenoids, alkaloids, carbohydrates, flavonoids, saponine, tannins, sterols, glycoside, cardiac glycoside, cyanogenic glycoside. Consuming foods rich in phytochemicals may reduce the risk of cardiovascular diseases.